Case report: Plasma exchange as a therapy for Miller-Fisher syndrome - Guan, Dongmei; Shan, Yuanzhuang; Zhang, Hailin (Frontiers in Immunology, 2025)
This is a report of an anti-GQ1b antibody-negative case of Miller-Fisher syndrome, presenting with diplopia and gait disturbance 3 days after catching a cold, accompanied by dizziness and headache, pain in the eyeballs and orbits, superficial sensory loss, ptosis, eye movements fixed in the middle of eyes, and limb weakness. Physical examination suggested that the patient had eye movements fixed in the middle of eyes, limb muscle strength was reduced, and the bilateral finger-to-nose and heel-knee-shin tests were clumsy and dysmetric. Assistant examinations showed albumin-cytologic dissociation in cerebrospinal fluid, incomplete bilateral facial nerve lesions, and negative anti-GQ1b antibody. After being treated with plasma exchange, the patient experienced slight improvement in eye adduction when she was discharged from the hospital and her diplopia and limb weakness were significantly improved. She could walk on her own without dizziness or headache and the pain in her eyeballs and orbits was completely relieved.